STUDI KOMPARASI KESIAPAN KERJA ANTARA PESERTA DIDIK KELAS XI JURUSAN AKUNTANSI DENGAN JURUSAN PEMASARAN SMKN 1 BENGKAYANG - Trifanny, Dela; Buwono, Sri; Basri, Muhammad (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
The thesis entitled "Comparative Study of Work Readiness Between Class XI Students of the Accounting Department and the Marketing Department of SMKN 1 Bengkayang" was conducted to determine whether there were differences in work readiness between accounting majors and marketing majors. This research is a quantitative research with comparative method. The subjects of this study were 32 class XI students majoring in accounting and marketing majoring respectively. Data were obtained using indirect communication techniques, namely by questionnaire/questionnaire and documentation. The results of the descriptive analysis show that although the average work readiness score for the accounting major is 76.98 compared to the marketing department, which is 75.89, after comparative analysis with the Independent T-test, the results show that there is no significant difference between the two majors. The results of the difference test showed that the significance value obtained was 0.364. sig. value 0.364 is greater than 0.05 so that in decision making H0 is accepted which means that there is no difference in the average work readiness score of the accounting major and the marketing major. These results also show that the educational program at SMKN 1 Bengkayang is able to prepare students to be ready to enter the workforce because this work readiness does not only exist in students from accounting majors but also in marketing majors.